Assistance in Learning to Read and Write Continuous Hijaiyyah Letters at TPQ Al Mu'min Jombang - Kalimatusyaro, Mei; Arif, Muhamad; Ma'arif, Muhammad Anas (LPPM, STAI Al-Azhar Menganti, 2023)
The aim of this community service is to provide knowledge about learning to read and write cursive hijaiyyah letters for late childhood children in the wustho class at TPQ Al Mu'min Jombang and to describe the results of learning to read and write cursive hijaiyyah letters for late childhood children in the wustho class. TPQ Al Mu'min Jombang. The result is that in learning activities, these methods are often combined into one so that learning is not monotonous and can attract students' attention to the material being presented. The material being taught is reading and writing continuous hijaiyyah letters and material on the Islamic religion such as fiqh, moral creed, tajwid,. Meanwhile, the media used in the learning process includes the Iqro' book volumes 1-6, whiteboard, markers, erasers, and a guide book for reading & writing Arabic letters. From the results of tests on reading and writing cursive hijaiyyah letters for children in the Wustho class TPQ Al Mu'min, it can be seen that the students' ability to read cursive hijaiyyah letters is classified as good with an average score of 74. Meanwhile, the ability to write cursive hijaiyyah letters for students is also relatively good with an average score -average 73.